Adenylate Cyclase and Phosphodiesterase Activity in the Platelet Release Abnormality - Chesney, Carolyn Mci.; Baker, Ann S.; Carvalho, Angelina Ca.; Ozer, Asli; Meissner, George F.; Colman, Robert W. (Thrombosis and Haemostasis, 1977)
11 patients with histories of clinical bleeding were selected as examples of platelet release abnormality. Mean bleeding time was 18 ± 2.6 min (normal ±SEM; 6 ±0.44); mean platelet adhesiveness was 9.9 ± 4.3% (normal ±SEM; 30 ±2.2). Clot retraction and platelet factor 3 were normal. Platelet aggregation with adenosine diphosphate (ADP), epinephrine and collagen was decreased, as was 14C-serotonin release. Electron microscopic studies of platelets exposed to epinephrine showed 2 subgroups: one which failed to aggregate or have centralization of organelles and a second which developed pseudopodia and centralization of organelles, but rarely aggregated or degranulated.Measurements of activity of adenylate cyclase and phosphodiesterase under basal conditions were performed on platelets from patients and control subjects. Adenylate cyclase activity was significantly lower and phosphodiesterase activity significantly higher in the patient group. Prostaglandin E1 was a potent stimulator of adenylate cyclase in both groups, as was NaF. It was concluded that the causative defects in patients with “platelet release abnormality” do not reside in either the activity of adenylate cyclase or of phosphodiesterase. Changes in formation and destruction of cyclic adenosinemonophosphate (AMP) may instead be regarded as a compensatory response to a defect in another effector system.